A Study on the Impact of Social Media Platforms on Online Retail Performance - Ha, Van Duong; Nguyen, Thi Thuy (Journal of Ecohumanism, 2024)
This study examines the impact of social media platforms (SMPs) on Vietnamese retailers’ online retail performance by inheriting factors from previous research models including: (i) Model of factors affecting behavioral intention of using SMPs include factors such as Functional Expectancy, Hedonic Motivation, Habit, Perceived Relationship; (ii) Model of factors affecting online retail performance includes factors such as Social Media Marketing Passive Approach, Social Media Marketing Active Approach, Social Media Marketing Engagement Approaches, Electronic Word-of-Mouth. At the same time, this study adds other factors such as Platform Usability, User Autonomy, Influencer Marketing to establish a research model. This study results show that Hedonic Motivation, Habits, Use Proficiently, Perceived Relationship have a positive impact on Behavioral Intention. The study results also show that Behavioral Intention, Social Media Marketing Active Approach have a positive impact on Behavioral Intention, and Platform Usability has a negative impact on Retail Performance. These findings have some important implications. It is proposed that retailers, stakeholders, managers and SMPs provider identify the factors that affect SMPs on the online retail performance of Vietnamese retailers.